Heliculture - A Future Source of Food - K.M., Sujith; K, Bharghavi; M, Rajashekhar; B, Madhuri; C, Asritha; N, Priyanka; B, Keerthana; G, Akhil; K, Rahul Viswakarma (Chronicle of Bioresource Management, 2024)
Food is a basic human need, and access to an adequate quantity and quality of food is essential for survival and good health. Food security and nutritive food are vital for individual health, economic development, social stability, and global cooperation. Promoting food security and nutritive food production in a sustainable manner helps protect the environment by encouraging responsible agricultural practices, reducing waste, and conserving natural resources. Heliculture in enhancing food security depends on various factors, including proper farming techniques, market access, and cultural acceptance of snail meat as a food source. Additionally, efforts to promote snail farming should be integrated into broader food security and nutrition programs to have a meaningful impact on improving access to nutritious food for vulnerable populations.